EFEKTIVITAS MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII - Hana Hanifah Khairiyah; Teti Sobari; Mimin Sahmini (IKIP Siliwangi, 2023)
Learning how to write is one of the language skills that students must master. The goal of this research is to provide an insight of the effectiveness of problem based learning models for writing skills in descriptive materials in Grade VII. The methods used in this study are descriptive qualitative. The study subject came from class VII E of SMP Negeri 3 Cimahi. Based on the result, we can conclude that the 36 samples have a total score of 3182, corresponding to an average score of 88 and a percentage of the total score of 88,7% representing a very good category. This indicates that the problem based learning model is effective in improving writing skills in descriptive materials for Grade VII students.